Pre_GI : a dynamic Catalogue and set of computational tools for the ontology and stratigraphy of horizontally transferred genomic islands in bacterial genomes - Reva, Oleg N. (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.